2014
DOI: 10.1007/s12088-014-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evaluation of Blood Culture Patterns among Neonates Receiving Vancomycin

Abstract: The objective of this study was to assess the frequency of blood culture (BC) collection among neonates who received vancomycin. Demographic, clinical, microbiologic, and pharmacy data were collected for 1275 neonates (postnatal age 0-27 days) who received vancomycin at an Intermountain Healthcare facility between 1/2006 and 9/2011. Neonates treated with vancomycin had a BC collected 94 % (n = 1198) of the time, of which 37 % (n = 448) grew one or more bacterial organisms (BC positive). Of these, 1 % (n = 5) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Geographic variation in the incidence of MRSA infections have also been well described, [20][21][22] unlike other geographic areas, Utah did not experience a large increase in community-associated MRSA during the study period. 23,24 Unpublished 2014 internal Intermountain Healthcare laboratory data showed that MRSA wound culture rates in pediatric patients across the IH system were 28%, and 33% at the tertiary children' s hospital (K.K., unpublished observations). Unfortunately, inconsistent capture of wound cultures during the study period precluded analysis of this element in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic variation in the incidence of MRSA infections have also been well described, [20][21][22] unlike other geographic areas, Utah did not experience a large increase in community-associated MRSA during the study period. 23,24 Unpublished 2014 internal Intermountain Healthcare laboratory data showed that MRSA wound culture rates in pediatric patients across the IH system were 28%, and 33% at the tertiary children' s hospital (K.K., unpublished observations). Unfortunately, inconsistent capture of wound cultures during the study period precluded analysis of this element in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Centers vary widely in use of antibiotics for neonates, [28*, 34, 35, 36]. In a recent survey of guidelines for use of 41 antimicrobials in French NICUs, 1 to 32 different dosing regimens per drug were identified.…”
Section: Variations In Antimicrobial Practicementioning
confidence: 99%
“…We found that only 1% of neonates who received vancomycin had MRSA detected, which suggests that therapeutic drug monitoring and dosing adjustments may occur for a large number of children without evidence of MRSA. 10 As 71% of these neonates grew coagulase-negative Staphylococci, it is unknown whether an AUC 24 /MIC $400 or a trough concentration target of 10-15 or 15-20 mg/L (all of which were derived from studies of MRSA) is appropriate. Despite its discovery more than 50 years ago, many unanswered questions remain regarding the optimal use of vancomycin for pediatric populations.…”
Section: To the Editorsmentioning
confidence: 99%
“…[7][8][9] A generic formulation of EFV has recently been approved by European Medicines Agency (EMA) according to results of a bioequivalence study done in healthy volunteers. 10 However, evidence is available showing that this population may not adequately reflect what happens in HIV-infected patients in terms of antiretroviral drugs pharmacokinetics. 11,12 Moreover, the single-dose cross-over design, adopted in bioequivalence studies, is a condition far from the real-life scenario.…”
Section: Comparison Of the In Vivo Pharmacokinetics And In Vitro Dissmentioning
confidence: 99%